Exploring dimensions of social support and resilience when providing care at the end of life: a qualitative study. (2nd September 2019) - Roper, Louise; Donnellan, Warren; Hanratty, Barbara; Bennett, Kate
Abstract: Background: Research shows that formal and informal social support can facilitate resilience in carers. There is a paucity of research exploring social support and resilience amongst recently bereaved informal carers. Aim: To examine how the presence or absence of distinct dimensions of social support facilitate or hinder resilience in recently bereaved informal carers. Participants: 44 bereaved carers, who had been identified by GP as 'main carer' of someone recently deceased (3–12 months), aged between 38 and 87 years old (mean= 67). Methods: Thematic analysis then the Ecological Framework of Resilience as an organisational tool to develop overarching themes in the data. We used the Sherbourne and Stewart model to identify social support that was lacking as well as social support that was present. Results: A range of social support types were identified. There was an emphasis on the importance of relationships with both health professionals and family members, including the care recipient. However, social support was not necessary for resilience if the participant had other resources. Conclusions: Social support for carers providing end of life care is almost exclusively based around end of life care 'work'. In comparison to other research our study suggests that relationships with family and health professionals are paramount. Multidimensional support is needed for carers to enhance their resilience.